The role of enterprise principles in shaping management duties at times of crisis - Mevorach, Irit (Cambridge University Press, 2013)
The enterprise group form presents special risks of mismanagement when entities in the group are in financial trouble. At the same time, pursing a group interest might assist in resolving the financial difficulties. In any event, delineating rules for this situation is challenging, given the variety of group structures and potential erosion of the benefit of limited liability when the regulation targets the whole group. The conflict is between “entity law” (which addresses each group entity separately) and “enterprise principles” (which address the group as a whole). There is scope for crafting the “wrongful trading” provision, now being adopted as an international standard, to accommodate the group scenario. In this context, enterprise principles should function only to help ascertain the commercial reality, rather than to override entity law.